2014
DOI: 10.1200/jco.2012.48.5797
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Major Molecular Response As a Trigger for Restarting Tyrosine Kinase Inhibitor Therapy in Patients With Chronic-Phase Chronic Myelogenous Leukemia Who Have Stopped Imatinib After Durable Undetectable Disease

Abstract: Loss of MMR is a practical and safe criterion for restarting therapy in patients with CML with prolonged CMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
421
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(439 citation statements)
references
References 13 publications
14
421
3
1
Order By: Relevance
“…In the ISAV study 48% of patients relapsed, with an overall risk of relapse at 36 months of 52%. The fact that imatinib can be interrupted was already demonstrated in other trials such as the STIM and the TWISTER studies [16][17][18]22,23]. The relapse of approximately 50% of patients after 2 years of FUP is now a consistent figure across several studies, including patients treated with second generation TKIs [24].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the ISAV study 48% of patients relapsed, with an overall risk of relapse at 36 months of 52%. The fact that imatinib can be interrupted was already demonstrated in other trials such as the STIM and the TWISTER studies [16][17][18]22,23]. The relapse of approximately 50% of patients after 2 years of FUP is now a consistent figure across several studies, including patients treated with second generation TKIs [24].…”
Section: Discussionmentioning
confidence: 92%
“…Despite this indication, several interruption studies showed that it is possible to safely interrupt imatinib treatment without experiencing progression of disease [13][14][15]. The STIM trial, the largest interruption study so far, showed that approximately 40% of patients maintained CMR [16,17]. The majority of the relapses (58%) occurred in the first 6 months after imatinib interruption.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been noted in this study and others that patients with low level positivity for BCR-ABL transcripts may be able to remain off therapy with only close monitoring. This was recently addressed systematically by French investigators, where it appeared safe and effective to only resume patients on TKI therapy if their transcript level became >0.1% (i.e., loss of MMR) [75].…”
Section: Treatment Duration and Discontinuationmentioning
confidence: 99%
“…For example, early case reports of TFR using lower thresholds for cessation-such as major cytogenetic response, CCyR, or MMR-demonstrated high rates of molecular and/or cytogenetic relapse, with nearly all patients relapsing following TKI cessation [47][48][49]. In studies of patients achieving deeper molecular responses, relapse in TFR was less frequent, occurring in approximately one-half to two-thirds of patients following frontline imatinib cessation [28,45,50,51]. The particular level of deeper molecular response required for successful TFR following TKI therapy is not yet known.…”
Section: Clinical Tfr Studies With Imatinibmentioning
confidence: 99%
“…The particular level of deeper molecular response required for successful TFR following TKI therapy is not yet known. Factors that are potentially predictive of relapse in TFR (e.g., time to BCR-ABL1 negativity, sex, Sokal risk score, duration of imatinib treatment prior to TFR) have been evaluated in several studies but without consistent results [28,51,52].…”
Section: Clinical Tfr Studies With Imatinibmentioning
confidence: 99%